Do Value Added Intellectual Coefficient and Corporate Governance Contribute to Firm's Economic Value Added - Hatane, Saarce Elsye; Agustin, Maria; Kana, Vera Radja; Dautrey, Jean Marc (Master of Management Study Program, Faculty of Business and Economics - Petra Christian University, 2019)
This study is about examining the influence of Intellectual Capital and Corporate Governance to EVA. Data used in this study were collected from a sample of 121 consumer goods companies in Indonesia and Malaysia from 2010 to 2017. Panel data multiple regression was performed to examine the research framework. The intellectual capital was measured by VAIC value, while the corporate governance was explained by the audit committee, remuneration board, and auditor quality and tenure. This study found that HCE, SCE, audit committee gender, remuneration size and remuneration gender had no effect on EVA in both Malaysian and Indonesian companies. In contrast, the audit committee size was found to affect the EVA of the companies in both countries. The CEE affected the company value of Malaysian companies while it had no effect on Indonesian companies. Audit quality and audit tenure had a positive effect only on Malaysian companies and none on Indonesian companies. This study used limited variables and a narrow business sector, thus the future research may expand the research model for other types of industries and apply the model in other countries.